Pembuatan Hotel Lebah Kelulut (Trigona sp.), Komoditas Unggulan Green Economy: Kelulut Hotel (Trigona sp.), Green Economy Leading Commodity - Adiwena, Muh.; Nurjannah, Nurjannah; HM, Irawati; Pandiangan, Gabriel Valentino; Andi, Andi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The honey green economy commodities focus on sustainable development that integrates economic, social, and environmental aspects that improve people's welfare while maintaining environmental sustainability. Not only produce honey, Trigona also plays a role in fertilizing plants as a pollinator that affects the quality of fruit and seed. Raising a green economy based on Kelulut bee honey is faced with various challenges, and the need for more information on nonoptimal cultivation and management. Therefore, this activity aims to solve this problem. This activity has several stages: surveys, focus group discussions, socialization, technical guidance, bee's hotel installation, and evaluation. Binalatung Mandiri Farmers Group has 27 members and lives in Kampung I/SKIP Village, Tarakan City. Since 2018, they have been cultivating kelulut bees. The current problem in cultivating kelulut bees is inappropriate storage locations for artificial and maintenance of the hives. The resolution starts with socialization and technical guidance about the bioecology of kelulut bees, calculating breakeven points in rupiah, and calculating the minimum sales that must be achieved based on profit targets. Artificial nests are named hotels because they carry the philosophy of being more profitable, long-lasting, and easy to move. The evaluation results concluded that bee hotels can increase honey production and have better durability than hives.